Role of Communication Skills in Facilitating Transformational Leadership in the Indian Workplace (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The role of communication skills in facilitating transformational leadership in the Indian workplace is a critical area of study, given the unique cultural, economic, and social dynamics of India. Transformational leadership, characterized by the ability to inspire, motivate, and foster innovation among employees, relies heavily on effective communication. This abstract explores how communication skills contribute to the success of transformational leaders in the Indian context. In the Indian workplace, which is marked by diverse languages, hierarchical structures, and a collectivist culture, communication becomes a pivotal tool for leaders to connect with their teams. Effective communication skills enable leaders to articulate a clear vision, foster trust, and encourage a collaborative environment. These skills include active listening, emotional intelligence, cultural sensitivity, and the ability to provide constructive feedback. The study examines various dimensions of communication, such as verbal and non-verbal communication, the use of technology-mediated communication, and the importance of bilingual or multilingual proficiency. It also highlights the challenges faced by leaders in overcoming communication barriers and suggests strategies for improvement. Empirical evidence from Indian organizations indicates that leaders who excel in communication are more successful in driving organizational change, enhancing employee engagement, and achieving high performance. The findings underscore the need for leadership development programs in India to prioritize communication skills training.